Smart and sustainable cities in the Mediterranean region: The contribution of short supply chains of food - Dos-Santos, M. J. P. L.; Baptista, N.; Machado-Santos, C. (Ecocycles, 2021)
The cities around the world in general, and in the Mediterranean area in particular, are facing tremendous challenges at the environmental, social, economic, and institutional levels, due to the urbanization trend, environmental climatic changes and challenges due to the ongoing COVID-19 pandemic. Therefore, cities need to be sustainable and smart in the future. An economically important and innovative sector in urban areas is food security. Nowadays, most of the literature explores the concept of smart cities from the point of view of information and communications technology, indeed, the connection with the sustainability aspects of the food supply chain and the ways to operationalize that, remains unsolved. This paper tries to overcome this gap in the literature. The main aim is to analyze the contribution of the short supply chain of food in terms of sustainability in smart cities, regarding current urban trends in cities in general and in Mediterranean areas in particular. The methodology was based on a literature review and includes quantitative and qualitative analysis. The results confirm the existence of positive impacts in the short supply chains of food in urban areas in terms of sustainability. Despite the existence of a considerable number of papers about smart cities and ICT-related topics, the benefits from society of short supply chains of food, and the linkage among the topics and subjects, remain unreferred to or with a limited knowledge exchange. The conclusions of this paper will be helpful for public decision makers to implement policies in order to promote the sustainability of Mediterranean cities.